GEDUNG PERTUNJUKAN SENI TRADISIONAL PEKALONGAN SEBAGAI REPRESENTASI CITRA KAWASAN JETAYU - Amrina Rosyada; Muhammad Asrori; Samsudi Samsudi (Universitas Sebelas Maret Surakarta, 2015)
The theater in Pekalongan as image representation Jetayu area is a building that facilitates the activities of traditional art performances Pekalongan, including dance, theater, music and craftsmanship. The building is planned to be in Jetayu region, an area in the old town of Pekalongan which has a function as a social and cultural areas. The problem that appears is how to strengthen its image as a socio-cultural areas through the provision of traditional art container, which is based on the needs of the city will be the facility's appreciation of traditional art and also able to represent the visual image of the area. In maintaining harmony in the area of visual culture and support the activities contained, planned design concept using contextual architecture of the display area of the visual characteristics such as the Dutch colonial building, and the application of acoustic systems to support arts activities that accommodated. As a result, the building is expected to be a means of traditional performing arts facility that is adequate as well as being a reflection and cultural elements in the cultural area Jetayu in the application form and function of the building that takes into account the visual and aesthetic character raised by the region.Keywords: Traditional Arts, Performance Building, image representation, Contextual Architecture.